Understanding pathways of dissimilatory and assimilatory dissolved inorganic nitrogen uptake in streams - M. Ribot; D. von Schiller; E. Martí (Limnology and Oceanography, 2017)
Dissolved inorganic nitrogen (DIN) in streams is mostly available as two different species: nitrate ( ) and ammonium ( ). These two DIN species undergo specific dissimilatory uptake pathways and show distinct preference during biological assimilation. These differences ultimately dictate how DIN is cycled within streams and its further export to downstream ecosystems. Here, we provide a synthesis analysis of the uptake of and at the reach scale and on the contribution of dissimilatory and assimilatory uptake pathways. We combined 15 N‐tracer experiments in a single stream with compiled results of and uptake from the literature. As expected, streams were more efficient in processing than at the reach scale. These results were partially explained by the fact that, on average, dissimilatory uptake (i.e., denitrification and DNRA) had a low incidence on total uptake, whereas dissimilatory uptake (i.e., nitrification) contributed to a high proportion of total uptake thereby increasing in‐stream concentration. Furthermore, assimilatory uptake by in‐stream biotic compartments dominated the total uptake of the two DIN species and was generaly higher for than for . Overall, results from this study indicate that assimilatory uptake by biotic compartments rather than permanent removal dominates total uptake in streams. In contrast, both assimilatory and dissimilatory uptake can contribute similarly to total uptake. Our findings have strong implications for a better understanding of N cycling within the context of widespread increases in DIN concentration and changes in the : ratio driven by human activities.